Estudo da adsorção de n-parafinas em materiais microporosos utilizando leito fixo - Silva, Allison Gonçalves (2008)
The oil produced in the fields of the Bahia State Brazil, has peculiar characteristics due to its high paraffin content. The produced oil is processed in the Landulfo Alves Refinery RLAM. The n-dodecane is a precursor in the production of the LAB - Linear Alquilbenzene, that is the main component for manufacture of biodegradable detergents. This n-paraffin is gotten of a refining chain, in vapor phase in the kerosene band, through an industrial recovery process called IsoSiv that it uses as adsorbent the 5A zeolite. In this work a study of the adsorption of n-paraffins is presented analyzing rupture curves using as adsorbent material the commercial 5A zeolites and a microporous material ALPO4 17 - prepared in laboratory. ALPO4 17 can be a substitute more selective than the 5A zeolite in this separation. An experimental apparatus was mounted for the accomplishment of adsorption tests in a fixed bed column. Through an experimental design of factorial type 2³ plus star configuration and accomplishment of three experiments in the central point, was possible to get a more including study of the entrance factors influence: concentration in the band of 3,17 to 37% n-dodecane (m/m), flow rate of 0,14 to 6,87 mL.min -1 and the temperature of 233 to 317 ºC, on the reply variable adsorption capacity (g/100g) relative 5A zeolite. Some physical and textural properties (diffraction of X-rays, specific area and mean pores diameter) of the adsorbents had been gotten and related with data of the literature. The experimental data illustrated that, amongst the studied entrance variables, the temperature and the concentration had presented significant effect in the values of adsorption capacity. The capacity values calculated for the 5A zeolite are in the band of 4 the 8 g/100g. The comparison of the capacities of adsorption of n-dodecane on the 5A zeolite and on the ALPO4-17 was made in the conditions of 15 % (m/m) of n-dodecane, 1mL.min-1 of flow rate and temperature of 300ºC. Through the adsorption test of n-dodecane in ALPO4-17 it was verified that the adsorbed maximum capacity was of 4,3g/100g. It also were realized tests in bicomponent systems of the mixtures C10-C11 and C12-C13, in the following conditions: concentration of 15 % (m/m), flow rate of 1mL.min-1, varying the operating temperature of 250 to 300ºC. It was verified a adsorbent selectivity for composites of more carbonic chain